Predictive Value of C-Reactive Protein-to-Albumin Ratio for Neonatal Sepsis - Li T; Li X; Wei Y; Dong G; Yang J; Yang J; Fang P; Qi M (Dove Medical Press, 2021)
Tiewei Li,1,* Xiaojuan Li,1,* Yulei Wei,1 Geng Dong,1 Jianwei Yang,1 Junmei Yang,1 Panpan Fang,1 Minglu Qi2 1Zhengzhou Key Laboratory of Children's Infection and Immunity, Children's Hospital Affiliated to Zhengzhou University, Henan Children's Hospital, Zhengzhou Children's Hospital, Zhengzhou, People's Republic of China; 2General Hospital of Taiyuan Steel (Group) Co., Ltd., Taiyuan, 030000, People's Republic of China*These authors contributed equally to this workCorrespondence: Panpan FangZhengzhou Key Laboratory of Children's Infection and Immunity, Children's Hospital Affiliated to Zhengzhou University, Henan Children's Hospital, Zhengzhou Children's Hospital, 33M Waihuan East Road, Longhu, Zhengzhou, 450018, People's Republic of ChinaTel +8637185515779Email fang_panpan@163.comMinglu QiGeneral Hospital of Taiyuan Steel (Group) Co., Ltd., No. 7, South 2nd Lane, Yingxin Street, Jiancaoping District, Taiyuan City, 030008, People's Republic of ChinaTel +863512139774Email feiyuxiaotian109@163.comPurpose: Previous studies have reported that C-reactive protein-to-albumin ratio (CAR) was a risk factor for sepsis in adults. However, little is known regarding the role of CAR in neonates with sepsis. The aim of this study was to explore the relationship between CAR and neonatal sepsis.Patients and Methods: In this research, from January 2016 to February 2020, a total of 1076 neonates were enrolled at Henan Children's Hospital in China. Complete clinical and laboratory data were collected. To identify the potential independent risk factor for neonatal sepsis, multivariate logistic regression analysis was performed. Receiver operating characteristic (ROC) curve analysis was used to evaluate the prediction accuracy of CAR in identifying neonatal sepsis.Results: CAR levels were higher in neonates with sepsis and showed a gradual increase among the control group, mild sepsis group and severe sepsis group. The prevalence of neonates with overall sepsis, mild sepsis and severe sepsis increased significantly from CAR tertile 1 to tertile 3. Multiple logistic regression analysis showed that CAR was an independent risk factor for the presence of sepsis (OR = 10.144, 95% CI 4.151- 24.790, P < 0.001) and severe sepsis (OR = 1.876, 95% CI 1.562- 2.253, P < 0.001). ROC curve analysis showed that CAR had a well discriminatory power in predicting sepsis (area under curve (AUC) = 0.74, 95% CI, 0.71- 0.77, P < 0.001) and severe sepsis (AUC = 0.70, 95% CI, 0.67- 0.74, P < 0.001).Conclusion: CAR was an independent predictor for the presence and severity of neonatal sepsis.Keywords: C-reactive protein-to-albumin ratio, neonatal sepsis, risk factor, severe sepsis